Main security measures for the protection of information and data in the cloud: a systematic review - Lezcano Gil, Alfredo José (2023)
The systematic review conducted focuses on identifying the main security measures to protect information and data in cloud computing environments. The objective was to highlight the importance of implementing robust security measures and explore their practical applicability. Relevant articles were selected and their results were analyzed through the PRISMA methodology. The findings emphasize the importance of strong password policies, access control, biometric and multifactor authentication, and the use of firewalls. In addition, specific solutions such as SSH key management in AWS and the adoption of CASB to strengthen cloud security were examined. Finally, it was determined that data encryption, access control, and biometric and multifactor authentication are crucial measures to protect information in the cloud. These measures prevent security breaches and ensure user privacy. Practical applications include robust password policies, multifactor authentication, and data encryption.